Construction of recombinant sox2-encoding plasmids that regulate pluripotency of breast cancer stem cells from indonesian patient - Hanifah Rahmi; Tiodinar Theresia; Amarila Malik; Septelia Inawati W (Universitas Ahmad Dahlan, 2019)
A therapy development with recombinant protein is a new and potential innovation to destroy cancer stem cells (CSCs). Various ways of killing CSCs include the provision of polyvalent anti-protein antibodies that code pluripotency. Therefore, it takes a mixture of Oct-4, c-Myc, Sox2, and Klf4 protein antigens that can stimulate the formation of polyvalent antibodies. This study aimed to construct Sox2 recombinant by identifying the target genes by reverse transcriptase PCR and then arranging their designs to be inserted into the cloning vector pET101/D-TOPOÂ®. The target gene was developed by finding the complete sequences of Sox2 nucleotides on the NCBI GenBank. The growth on LB-ampicillin agar plates was amplified by PCR to obtain colonies with pET101/D-TOPOÂ® vectors and inserts of the pluripotent gene of CSCs, then the PCR results were observed through electrophoresis. A total of fifteen colonies have DNA bands with a base pair of about 300 bp in length. The recombinant clones produced Sox2 genes with a base length of 330 bp.